A review of studies evaluating medical cannabis for the chronic pain management - Justyna Żyga (Kazimierz Wielki University, 2022)
Introduction: Medical cannabis for patients with chronic pain related to various conditions has been the focus of numerous investigations. Cannabis-based medicine has been described for hundreds of years but only recently have we seen the more scientific, evidence-based approach to its use, and ongoing investigations continue to explore its potential medical benefits.  State of knowledge: As the results of studies assessing medical cannabis in pain alleviate seem promising, only weak recommendations are available. Important factors to consider in the development of guidelines include optimal doses, routes of administration and used types of cannabinoids. In discussed studies no serious adverse events were reported and treatment was well tolerated by participants. Conclusions: Evidence suggests that cannabis-based medicine can be safe and effective in pain relief. Further high-quality randomised clinical trial studies are needed. It is important to assess the safety profile of each individual cannabinoid formulation and define the population that can benefit from cannabis therapy for establishment of prospective recommendations and guidelines.